2010
DOI: 10.1289/ehp.0901143
|View full text |Cite
|
Sign up to set email alerts
|

Formaldehyde Exposure and Asthma in Children: A Systematic Review

Abstract: ObjectiveDespite multiple published studies regarding the association between formaldehyde exposure and childhood asthma, a consistent association has not been identified. Here we report the results of a systematic review of published literature in order to provide a more comprehensive picture of this relationship.Data sourcesAfter a comprehensive literature search, we identified seven peer-reviewed studies providing quantitative results regarding the association between formaldehyde exposure and asthma in chi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
99
0
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 240 publications
(108 citation statements)
references
References 28 publications
1
99
0
8
Order By: Relevance
“…The first longitudinal study on the respiratory effects of indoor formaldehyde found a significant positive association between formaldehyde concentration and incidence of asthma diagnosis (OR 1.7, 95% CI 1.1-2.6, for each formaldehyde increment of 10 mg?m ), but only among non-atopic children [69]. In a recent meta-analysis, McGWIN et al [129] calculated a 17% increase in the risk of asthma (OR 1.17, 95% CI 1.01-1.36) for each 10 mg?m -3 unit increase in formaldehyde concentration. Lastly, there is some convincing evidence of an effect of formaldehyde in asthma morbidity, such as respiratory symptoms or lung function [35,106,125,128,[130][131][132].…”
Section: Formaldehyde and Vocsmentioning
confidence: 99%
“…The first longitudinal study on the respiratory effects of indoor formaldehyde found a significant positive association between formaldehyde concentration and incidence of asthma diagnosis (OR 1.7, 95% CI 1.1-2.6, for each formaldehyde increment of 10 mg?m ), but only among non-atopic children [69]. In a recent meta-analysis, McGWIN et al [129] calculated a 17% increase in the risk of asthma (OR 1.17, 95% CI 1.01-1.36) for each 10 mg?m -3 unit increase in formaldehyde concentration. Lastly, there is some convincing evidence of an effect of formaldehyde in asthma morbidity, such as respiratory symptoms or lung function [35,106,125,128,[130][131][132].…”
Section: Formaldehyde and Vocsmentioning
confidence: 99%
“…Recent studies report associations between in-home formaldehyde concentrations and childhood asthma (McGwin et al 2010;Dannemiller et al 2013), and formaldehyde is classified as a human carcinogen (NTP 2011). Formaldehyde concentrations in US residences regularly exceed benchmarks established for health protection (Logue et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…10,11 It causes vomiting, diarrhea and abdominal pain and larger doses may cause decreased body temperature, shallow respiration, weak irregular pulse and even blindness. 12 It is reported to have the potential effect of significantly mis-folding DNA, RNA and native soluble proteins into insoluble fibrils comprising of cross-ß-sheet and oxidizing proteins with the attendant amyloid fibrillation and increase in acid levels in the blood even if it remains in the human body for only a short time. 13 Inhaled formaldehyde gas is reported to have negative effects on the central nervous system, and these effects may appear in the form of insomnia, lack of concentration, memory loss, loss of appetite, and mode/balance alteration.…”
Section: Introductionmentioning
confidence: 99%